2008
DOI: 10.1002/cbic.200800219
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Additional Players in the Alternative Biosynthesis Pathway to Isovaleryl‐CoA in the Myxobacterium Myxococcus xanthus

Abstract: Isovaleryl-CoA (IV-CoA) is usually derived from the degradation of leucine by using the Bkd (branched-chain keto acid dehydrogenase) complex. We have previously identified an alternative pathway for IV-CoA formation in myxobacteria that branches from the well-known mevalonate-dependent isoprenoid biosynthesis pathway. We identified 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) synthase (MvaS) to be involved in this pathway in Myxococcus xanthus, which is induced in mutants with impaired leucine degradation (e.g., b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 58 publications
3
65
0
5
Order By: Relevance
“…This second BKD activity might be a side activity of the pyruvate dehydrogenase or a related chemical oxidative decarboxylation, as no second bkd locus could be identified in the genome (unpublished results). Moreover, growth of HB002 is not MVL dependent because the block in the alternative pathway does not affect isoprenoid biosynthesis, as liuC encodes a dehydratase/hydratase that is involved in the conversion of HMG-CoA to 3-methylglutaconyl-CoA and vice versa (4). As expected, the FA profile (4) as well as the developmental phenotype (data not shown) can be complemented (Fig.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…This second BKD activity might be a side activity of the pyruvate dehydrogenase or a related chemical oxidative decarboxylation, as no second bkd locus could be identified in the genome (unpublished results). Moreover, growth of HB002 is not MVL dependent because the block in the alternative pathway does not affect isoprenoid biosynthesis, as liuC encodes a dehydratase/hydratase that is involved in the conversion of HMG-CoA to 3-methylglutaconyl-CoA and vice versa (4). As expected, the FA profile (4) as well as the developmental phenotype (data not shown) can be complemented (Fig.…”
supporting
confidence: 66%
“…All (4), and FA analysis as well as myxobacterial fruiting body formation has also been described previously (26).…”
mentioning
confidence: 94%
“…We speculate that the transporter mutant is unable to utilize BCAAs, preventing growth, and it therefore displays a deficiency in predation. Moreover, it has been shown that BCAAs, such as leucine, serve as the precursor for fatty acid biosynthesis and also as starter molecules for polyketide synthases (41,42). Reduced levels of available BCAAs due to disrup-tion of the ABC transporter could result in an altered specialized metabolite or fatty acid profile and generate deficits in growth on otherwise-suitable prey.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most frequent transposon insertion sites (11 independent isolates) occurred in MXAN_5713, encoding an ABC transporter/permease predicted to be involved in branched-chain amino acid (BCAA) transport. BCAAs are essential to M. xanthus and function as precursors for fatty acid synthesis as well as specialized metabolite production (31,41,42). All 11 transposon insertion mutations in MXAN_5713 displayed an LOF phenotype (see Fig.…”
Section: Identification Of M Xanthus Predation Mutants Following a Tmentioning
confidence: 99%
“…In addition, pivalic acid (or pivalyl-CoA) might be formed during catabolism of marine sponge-derived polytheonamides in which the tert-butyl modification of threonine is introduced post-translationally (28). Isovaleryl-CoA is produced during leucine catabolism via the branched chain keto acid dehydrogenase or in myxobateria, via a mevalonate-dependent isoprenoid biosynthesis pathway involving 3-hydroxy-3-methylglutaryl-CoA synthase (29). In several bacteria, the gene encoding IcmF is coregulated with those involved in branched-chain amino acid degradation (30) or fatty acid catabolism (13).…”
Section: Discussionmentioning
confidence: 99%